A role of peroxisome proliferator‐activated receptor γ in non‐alcoholic fatty liver disease - Skat‐Rørdam, Josephine (Basic Clin Pharmacol Toxicol, 2019)
Non‐alcoholic fatty liver disease is becoming a major health burden, as prevalence increases and there are no approved treatment options. Thiazolidinediones target the nuclear receptor peroxisome proliferator‐activated receptor γ (PPARγ) and have been investigated in several clinical trials for their potential in treating non‐alcoholic fatty liver disease (NAFLD) and non‐alcoholic steatohepatitis (NASH). PPARγ has specialized roles in distinct tissues and cell types, and although the primary function of PPARγ is in adipose tissue, where the highest expression levels are observed, hepatic expression levels of PPARγ are significantly increased in patients with NAFLD. Thus, NAFLD patients receiving treatment with PPARγ agonists might have a liver response apart from the one in adipose tissue. Owing to the different roles of PPARγ, new treatment strategies include development of compounds harnessing the beneficial effects of PPARγ while restricting PPARγ unwanted effects such as adipogenesis resulting in weight gain. Furthermore, dual or pan agonists targeting two or more of the PPARs have shown promising results in pre‐clinical research and some are currently proceeding to clinical trials. This MiniReview explores adipose‐ and liver‐specific actions of PPARγ, and how this knowledge may contribute in the search for new treatment modalities in NAFLD/NASH.